Assessing the Brazilian Regional Economic Structure: a spatial output decomposition analysis - Fernando Perobelli; Eduardo Haddad; Vinicius Almeida (European Regional Science Association (ERSA), 2012)
The use of an interregional input-output model enables us to better understand the regional economic structure of production. It provides a rich and detailed static picture of a specific economy. We can implement a comparison overtime and across space. The second one will be implemented in this paper and enables an assessment of the differences in economic structure across regions. (Jackson and Dzikowski, 2002). The main aim of this paper is assessing structural change and interregional structural differences among Brazilian regions. The method applied in this paper uses the interregional input-output matrix for Brazil. This matrix considers 27 regions and 56 sectors in each region. Using this data set it will be possible to decompose differences in gross output into two distinct categories. The variation in gross output can be a function of the technical structure of production and of the final demand characteristics. The method provides a measure of the differences in interindustry structure among regions and also provides a measure of the way in which differences in interindustry structure and final demand distributions differentiate production across. The decomposition implemented in this paper is a variation of the method implemented by Feldman et al (1987). The spatial output decomposition (SOD) will be used to explore output differences between each region in Brazilian economy and an "average" Brazilian region. For each Brazilian state we will use SODL method that compares a state to an average Brazilian interindustry coefficient table and an average vector of final demand levels. The SODL method, emphasizes differences in the sizes of the state economies. : spatial output decomposition, Brazilian economy; regional economic structure
Keywords: R15; 330